Teenage Mutant Ninja Turtles. vol. 1, Change is constant - Eastman, Kevin B.; Waltz, Tom.; Duncan, Dan, 1982- (San Diego, Calif. : IDW, 2012)
It's a different world for the Turtles. The group is broken as Raphael wanders the streets of NYC in search of food and shelter. His brothers and Master Splinter are on the search, but so far all they can find is trouble - in the form of mutant alley cat Old Hob and his gang of criminals -- cover.
Originally published as Teenage Mutant Ninja Turtles issues #1-4.
Keywords: Teenage Mutant Ninja Turtles (Fictitious characters) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Graphic novels